Towards Understanding Employability in the Indian Context: A Preliminary Study. (March 2015) - Pandit, Shilpa Ashok; G., Preethi; Wallack, Dave C.; C., Vijayalakshmi
The article reports a year-long study to systematically understand 'employability' as a social psychological construct and its linkages with various person centred attributes and choice of career tracks. To that end, the article is divided into three sections. The first section analyses the Indian context of the demographic dividend and higher education and locates the construction of employability within it. The second section reports the rationale, the method and the results. Finally, the article concludes with the discussion of results and implications. Employability has a duality associated with it. It is a construct that, on one hand, is sensitive to macro variables like the state of the economy, the access to education and finance and sector-wise trends. On the other hand, employability may also be related to the person-centred variables like effectiveness and hope. The recruitment process can be seen as a site of this interaction between structural trends and agentic competencies. Through understanding the duality of structure and agency can we centre the debate on employability, skewed away from economic and sociological factors to psychological ones. This article is an attempt in that direction. In the present study, based on preliminary field research, six career tracks were identified. 643 students from final/pre-final semesters in colleges and employed cohort from Thanjavur and Chennai in Tamil Nadu, were administered psychological instruments regarding personal effectiveness and attribution to success and failure. Additionally, students were tested before and after the placement season to cross-validate whether they got employed or not. The model was tested using binomial logistic regression analysis. Results indicate that the employed cohort both as students and recently employed displayed significantly different internal and external attribution to success and failure and personal effectiveness than the non-employed cohort. Implications, limitations and future research questions are discussed.